The carbon storage benefits of agroforestry and farm woodlands - Upson, Matthew A. (Cranfield University, 2014)
Planting trees on agricultural land either as farm woodlands or agroforestry (trees integrated with farming) is one option for reducing the level of atmospheric carbon dioxide. Trees store carbon as biomass, and may increase carbon storage in the ground. A review of the literature outlined uncertainty relating to changes in carbon storage after planting trees on agricultural land. The aim of this thesis is to deter¬mine the impact of tree planting on arable and pasture land in terms of above and belowground carbon storage and thereby address these uncertainties, and assess the implications for the Woodland Carbon Code: a voluntary standard for carbon storage in UK woodlands. Measurements of soil organic carbon to a depth of 1.5 m were taken at two field sites in Bedfordshire in the UK: a 19 year old silvoarable trial, and a 14 year old silvopasture and farm woodland. On average 60% and 40% of the soil carbon (rel¬ative to 1.5 m) was found beneath 0.2 and 0.4 m in depth respectively. Whilst tree planting in the arable system showed gains in soil organic carbon (12.4 t C ha−1 at 0–40 cm), tree planting in the pasture was associated with losses of soil organic carbon (6.1–13.4 t C ha−1 at 0–10 cm). Evidence from a nearby mature grazed woodland indicate that these losses may be recovered. No differences associated with tree planting were found to the full 1.5 m, though this may be due to a lack of statistical power. Measurements of above and belowground biomass, and the root distribution of 19 year old poplar (Populus spp.) trees (at the silvoarable trial) and ash (Fraxinus excelsior) trees ranging from 7 to 21 years (at several field sites across Bedfordshire) were made, involving the destructive harvest of 48 trees. These measurements suggest that Forestry Commission yield tables overestimate yield for poplar trees grown in a silvoarable system. An allometric relationship for determining ash tree biomass from diameter measurements was established. The biophysical model Yield-SAFE was updated to take into account root growth, and was parameterised using field measurements. It was successfully used to describe existing tree growth at two sites, and was then used to predict future biomass carbon storage at the silvoarable trial. Measurements indicate that losses in soil carbon at relatively shallow depths can offset a large proportion of the carbon stored in tree biomass, but assessing changes on a site by site basis may be prohibitively expensive for schemes such as the Woodland Carbon Code.
Keywords: Agroforestry; Soil organic carbon; Woodland Carbon Code; Soil carbon fractionation; Yield tables; Modelling; Carbon storage